pradeepss wrote:

Shameek,

You have the correct expression for 1.

I read in

MGMAT guides as follow:

if square of Y = 1, then Y = + or - 1. GMAT approach is, if Y = 1 then square of Y = 1 and if Y = -1 the square if Y is still 1.

Hope that helps.

First of all I would like to know where does square of Y comes into picture in this question. If you open the 1st statement's expression you get

\(X*Y + (\frac{Y}{2}) = 1\)

which will be \(\frac{Y}{2} + \frac{Y}{2} = 1\)

i.e. Y = 1 - Hence Sufficient

For the second statement :-

Y*(2X-1) = 2X - Y

2XY - Y = 2X - Y

i.e. 2XY - 2X = 0

i.e. 2X(Y-1) = 0

either X = 0 or Y = 1

Given that \(X = \frac{1}{2}\) we are left with Y = 1

And yes \(\sqrt{Y^2} = |Y|\); and therefore 2 solutions for Y.

But why are you concerned with it for this question? I don't get that.

Also according to me the answer should be "D" not "B".